PERATURAN-PERATURAN DAERAH BERMUATAN MATERI AJARAN ISLAM DI SUMATERA SELATAN - Yazwardi, Yazwardi (Universitas Islam Negeri Raden Fatah Palembang, 2016)
Indonesia as a country that consists of areas in the various islands with mileage close of central administration necessitates the existence of local governance as mandated in Article 18 of the Constitution NRI 1945. Local regulations as an operational basis for carrying out local government administration functions and is part of a systematic law in Indonesia has a very significant role in regulating the life of the nation. Regional Regulation of the substance often causes controversy and resistance from various academics and social groups of society when loading material and the teaching of religious values. Some local regulations in South Sumatra Province who allegedly charged material Islamic teachings do not bring social problems because the material in parallel with its cargo historical circumstances, sociological, anthropological and demographic factors people of South Sumatra.